(untitled) (Ustozlar uchun, 2024)
Abstract This article delves into syntax, a critical branch of linguistics focused on the rules and principles governing the formation and structure of sentences. Syntax examines how words combine to form phrases, clauses, and sentences, exploring the hierarchical and functional relationships between different elements within a sentence. The study highlights key syntactic theories and models, such as generative grammar, and discusses the methods used to analyze sentence structure across various languages. Through theoretical exploration and empirical analysis, the article provides a comprehensive understanding of how syntax contributes to the organization of meaning in language.